Cyanotic congenital heart disease_effects of iron supplementation on hematological indices in iron-sufficient and iron-deficient children - Rambabu Sharma; Devendra Meena; Dhan Raj Bagri (Journal of Indian College of Cardiology, 2021)
Background: Cyanotic congenital heart disease (CCHD) children often have malnutrition and iron-deficiency anemia along with poor weight gain. Low arterial oxygen saturation due to CCHD affects hematological indices. Objective: The objective of the study is to find iron status and hematological indices in children having CCHD and to study the impact of iron therapy in the sample population under study. Materials and Methods: This hospital-based, prospective, cross-sectional, observational type of study evaluated 50 CCHD children aged more than 1 year with informed written consent from the parents. Sample size is calculated at 95% confidence level and alpha error 4.005 assuming 52.2% iron deficiency in patient with CCHD with hematocrit value <60%. Results: Tetralogy of Fallot was the most common CCHD followed by transposition of great arteries and tricuspid atresia. Most common age of presentation is <50 months with cyanosis (50%) and congestive cardiac failure (16%) with male preponderance (M:F = 3:1). 60% CCHD patients were iron deficient. Iron-deficient group shows significant improvement in all hematological parameters after iron supplementation compared with iron-sufficient group. Results and Discussions: Serum iron levels, serum ferritin levels, mean hemoglobin levels, total red blood cell count, hematocrit, and red cell distribution width along with red cell indices (mean corpuscular volume, mean corpuscular hemoglobin, and MCHC) should be used as diagnostic tool for the evaluation of iron status in patients as well as for monitoring improvement. This emphasizes that iron therapy iron must be supplemented with special focus on iron status of children.